Multi-Walled Carbon Nanotubes Functionalized with a New Schiff Base Containing Phenylboronic Acid Residues: Application to the Development of a Bienzymatic Glucose Biosensor Using a Response Surface Methodology Approach - Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (Springer, 2024)
An innovative supramolecular architecture is reported for bienzymatic glucose biosensing based on the use of a nanohybrid made of multi-walled carbon nanotubes (MWCNTs) non-covalently functionalized with a Schiff base modified with two phenylboronic acid residues (SB-dBA) as platform for the site-specific immobilization of the glycoproteins glucose oxidase (GOx) and horseradish peroxidase (HRP). The analytical signal was obtained from amperometric experiments at − 0.050 V in the presence of 5.0 × 10−4 M hydroquinone as redox mediator. The concentration of GOx and HRP and the interaction time between the enzymes and the nanohybrid MWCNT–SB-dBA deposited at glassy carbon electrodes (GCEs) were optimized through a central composite design (CCD)/response surface methodology (RSM). The optimal concentrations of GOx and HRP were 3.0 mg mL−1 and 1.50 mg mL−1, respectively, while the optimum interaction time was 3.0 min. The bienzymatic biosensor presented a sensitivity of (24 ± 2) × 102 µA dL mg−1 ((44 ± 4) × 102 µA M−1), a linear range between 0.06 mg dL−1 and 21.6 mg dL−1 (3.1 µM–1.2 mM) (R2 = 0.9991), and detection and quantification limits of 0.02 mg dL−1 (1.0 µM) and 0.06 mg dL−1 (3.1 µM), respectively. The reproducibility for five sensors prepared with the same MWCNT–SB-dBA nanohybrid was 6.3%, while the reproducibility for sensors prepared with five different nanohybrids and five electrodes each was 7.9%. The GCE/MWCNT–SB-dBA/GOx-HRP was successfully used for the quantification of glucose in artificial human urine and commercial human serum samples. Graphical Abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer-Verlag GmbH Austria, part of Springer Nature 2024.